Effects of fission and mitophagy on mitochondrial functionality under accelerated damage conditions: A mathematical modeling approach - Zamora-Ramírez, Ángel J.; Santillán, Moisés (Frontiers in Applied Mathematics and Statistics, 2023)
There is growing evidence that mitochondrial dynamics play a role in mitochondrial function quality control. Recent studies have discovered that physical activity can aid in maintaining a healthy mitochondrial population and may even counteract the mitochondrial damage caused by obesity by modifying mitochondrial dynamics processes like mitogenesis, fission, and mitophagy. However, the underlying mechanisms and how they influence the various processes of mitochondrial dynamics have not been completely clarified. This study seeks to make an initial effort to fill this gap by utilizing mathematical modeling to investigate how modifications to the processes involved in mitochondrial dynamics can aid in preserving a healthy mitochondrial population under conditions of accelerated damage. We found by analyzing the model stationary behavior that fission and mitophagy are strictly required for a healthy mitochondrial population, that increasing the rate of mitochondrial damage has a negative impact on the population of functional mitochondria, and that such damage can be mitigated to some extent by increasing fission and/or mitophagy rates. These findings are finally discussed in the context of the benefits of physical activity for mitochondrial population health in obese individuals.